Copper-bispidine-catalyzed aziridination: a new twist in small molecule activation - Bleher, Katharina; Comba, Peter; Gast, Michael; Kronenberger, Sandra; Josephy, Thomas (Inorganica chimica acta, 2022)
Described are copper(I) and copper(II) complexes of a series of tetradentate bispidine ligands together with their structural, spectroscopic and electrochemical properties. These complexes are efficient catalysts for the aziridination of styrene, and the efficiency is shown to be correlated to the CuII/I redox potential. While variation of the redox potential only leads to relatively small changes of the catalytic properties, it is shown that replacement of the in-plane tertiary amine of the bispidine scaffold by a secondary amine leads to an up to 1000-fold increase of the catalytic efficiency. In contrast, no significant increase of the catalytic performance is observed when the axial tertiary amine is replaced by a secondary amine. The effect of the in-plane substitution of the tertiary amine is shown to be related to a deprotonation at the secondary amine in presence of a base. This is demonstrated with a CuII acetonitrile complex for which a pKa value in MeCN of approx. 17.5 (corresponding to an approx. pKa value of 9.5 in H2O) was determined by spectrophotometric titration. It is proposed that the enhanced catalytic efficiency is due to deprotonation of the amine at the high-valent part of the catalytic cycle. This may lead to a stabilization of the nitrene form, but most important to a drastic improvement of the catalytic performance.